Transparency in Nigeria's Oil and Gas Industry: Is Policy Re-Engineering the Way Out? - Oyewunmi, Olabode A.; Olujobi, Olusola J. (International Journal of Energy Economics and Policy, 2016)
Nigeria is Sub-Saharan Africa's largest oil producer and also possesses huge unrealized gas deposits. The oil and gas industry is considered as the lifeblood of Nigeria's socio-economic development, bearing in mind the well-established historical antecedents and the unfolding happenings. However, inspite of the strategic role of this industry to national wellbeing, it is a signpost for; corruption, infrastructure deficit, oil smuggling, vandalism and diverse security challenges. It is noteworthy, that accurate revenues attributable to the industry are not consistently published. Royalties paid to the Federal Government remain undisclosed for unjustifiable reasons. Also, specifics of transactions are disguised, thereby making it practically impossible for an interested stakeholder to monitor the level of; royalties, taxes, fees and charges paid to the Federal Government. Hence, the paper critically assessed selected laws, code, practices and the essence of policy re-engineering to Nigeria's oil and gas industry. Conclusions and contextual recommendations were also proffered. Keywords: transparency, oil & gas, law, policy, re-engineering, Nigeria JEL Classifications: O13, Q48